2021
DOI: 10.3390/polym13172876
|View full text |Cite
|
Sign up to set email alerts
|

Void Content Minimization in Vacuum Infusion (VI) via Effective Degassing

Abstract: This paper addresses the major concern which component porosity represents in Vacuum Infusion (VI) manufacturing due to resin gelation at pressures close to absolute vacuum. Degassing is a fundamental step to minimize or even avoid resin outgassing and enhance dissolution of voids created during preform impregnation. The efficacy of different degassing procedures based on vacuum degassing, and assisted by adding a nucleation medium, High Speed (HS) resin stirring and/or later pressurization during different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…On the basis on the conducted investigations it was found that the best performance characteristics (the lowest weight and thickness -especially important in aircraft structures) are found in the material produced at the highest negative pressure value (1,0 bar). The best aesthetic properties (surface quality) are obtained with a laminate produced at an intermediate negative pressure value (0.7 bar) -visual inspection [18,21]. All the mechanical properties of the composite produced at the highest negative pressure value are clearly the best among the materials tested.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the basis on the conducted investigations it was found that the best performance characteristics (the lowest weight and thickness -especially important in aircraft structures) are found in the material produced at the highest negative pressure value (1,0 bar). The best aesthetic properties (surface quality) are obtained with a laminate produced at an intermediate negative pressure value (0.7 bar) -visual inspection [18,21]. All the mechanical properties of the composite produced at the highest negative pressure value are clearly the best among the materials tested.…”
Section: Discussionmentioning
confidence: 96%
“…The matrix of the examined composites was epoxy mixture resin L285 with H287 hardener [20], mixed in a ratio of 100: 40. The prepared composite material was vented using a negative pressure pump to remove unwanted air bubbles [18]. The composites were assembled and fabricated on a glass plate (Fig.…”
Section: Preparation Of Test Materialsmentioning
confidence: 99%
“…The very first result obtained from this thesis was a Spanish patent containing ISFLIP processing sequence and the main tooling systems [1]. Besides, a version of Chapter 4 has been submitted for publication in the Journal of Composite Materials [2], and a version of Chapter 5 has been also submitted for publication in the Journal of Composite Materials [3].…”
Section: Prefacementioning
confidence: 99%
“…Designs were kept as simple as possible while satisfying the required level of scientific soundness. Effects on specimen quality attributes of different filling and post-filling pressure conditions, and preform assemblies were addressed through two simple two-level factorial designs, 2 2 . A total of four design factors were analysed (Table 5.1): pressure increment (P), gradient of pressure (G), preform assembly (A) and inlet condition (I).…”
Section: Factorial Designsmentioning
confidence: 99%
See 1 more Smart Citation